1994
DOI: 10.1111/j.1432-1033.1994.tb20053.x
|View full text |Cite
|
Sign up to set email alerts
|

De novo Sulfation of l‐Tyrosine in HepG2 Human Hepatoma Cells and Its Possible Functional Implication

Abstract: HepG2 human hepatoma cells, labeled with [35S]sulfate in the presence of 10-30 pg/ml of cycloheximide, released up to 64% of the amount of free tyrosine-0-[35S]sulfate produced and released by cells labeled in the absence of cycloheximide. A time-course study revealed that, in cells incubated in medium containing [3H]tyrosine, free [3H]tyr~sine-0-sulfate was produced within 5 min of incubation, whereas no [3H]tyrosine-sulfated proteins were detected until 20 min after the incubation had begun. Using 3'-phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…A consensus formed (following Huttner's discovery of the widespread occurrence of the post-translational tyrosine sulfation of eukaryotic proteins (14)) is that free TyrS is generated primarily through the turnover of tyrosine sulfated proteins in vivo. We have indeed demonstrated earlier (16) that exogenous tyrosine 35 S-sulfated proteins added to the medium could be endocytosed by cultured cells and degraded intracellularly to generate free Tyr[ In our recent studies (19,20), we have obtained conclusive evidence that sulfation of L-p-tyrosine does occur in several mammalian cell lines. It is, however, unclear why mammalian cells should carry out the sulfation of an amino acid needed for protein synthesis.…”
Section: Expression Of the Cloned Rat Liver Dopa/tyrosine Sulfotransfmentioning
confidence: 53%
See 3 more Smart Citations
“…A consensus formed (following Huttner's discovery of the widespread occurrence of the post-translational tyrosine sulfation of eukaryotic proteins (14)) is that free TyrS is generated primarily through the turnover of tyrosine sulfated proteins in vivo. We have indeed demonstrated earlier (16) that exogenous tyrosine 35 S-sulfated proteins added to the medium could be endocytosed by cultured cells and degraded intracellularly to generate free Tyr[ In our recent studies (19,20), we have obtained conclusive evidence that sulfation of L-p-tyrosine does occur in several mammalian cell lines. It is, however, unclear why mammalian cells should carry out the sulfation of an amino acid needed for protein synthesis.…”
Section: Expression Of the Cloned Rat Liver Dopa/tyrosine Sulfotransfmentioning
confidence: 53%
“…Purification of the Rat Liver Dopa/Tyrosine Sulfotransferase-Preliminary experiments showed that similar to several mammalian cell lines previously studied (19,20), the Dopa/tyrosine sulfotransferase was present predominantly in the cytosolic fraction of the rat liver. The specific activity of the enzyme purified from the rat liver cytosol, with L-Dopa as the substrate, was determined to be 2,153 pmol/min/mg protein, indicating a 760-fold purification over its specific activity in the rat liver cytosol (Table I).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…To date, these in vitro assay systems have revealed the sulfation of numerous compounds including tyrosine, monoamine neurotransmitters, environmental hormones as well as three opioid drugs, buprenorphine, pentazocine, and naloxone (Kurogi et al, 2012, Liu et al, 2007, Sakakibara et al, 1994, Suiko et al, 2000). HepG2 human hepatoma cell line was used as a model of hepatocyte for the metabolic labeling experiment.…”
Section: Introductionmentioning
confidence: 99%